2006
DOI: 10.1111/j.1467-9280.2006.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Essences and the Reality of Mental Disorders

Abstract: Do people believe mental disorders are real and possess underlying essences? The current study found that both novices and practicing clinicians held weaker essentialist beliefs about mental disorders than about medical disorders. They were also unwilling to endorse the idea that mental disorders are real and natural. Furthermore, compared with novices, mental health clinicians were less likely to endorse the view that there is a shared cause underlying a mental disorder and that one needs to remove the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 27 publications
8
69
0
1
Order By: Relevance
“…Consistent with this interpretation, Rehder and Kim (2009) found a stronger causal status effect when observable features were given an explicit underlying cause (also see Rehder, 2003b). And, Ahn and her colleagues found that expert clinicians both view mental disorders as less essentialized than laypersons (Ahn, Flanagan, Marsh, & Sanislow, 2006) and exhibit only a weak causal status effect (Ahn, Levin, & Marsh, 2005), consistent with the idea that the causal status effect depends on diagnostic reasoning from observable features to underlying properties that are strongly associated with category membership.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with this interpretation, Rehder and Kim (2009) found a stronger causal status effect when observable features were given an explicit underlying cause (also see Rehder, 2003b). And, Ahn and her colleagues found that expert clinicians both view mental disorders as less essentialized than laypersons (Ahn, Flanagan, Marsh, & Sanislow, 2006) and exhibit only a weak causal status effect (Ahn, Levin, & Marsh, 2005), consistent with the idea that the causal status effect depends on diagnostic reasoning from observable features to underlying properties that are strongly associated with category membership.…”
Section: Discussionsupporting
confidence: 54%
“…In physicians, this reduction of essentialist beliefs was most evident in questions regarding treatment. Similarities and differences to the results from Ahn et al (2006) are discussed.…”
Section: Introductionsupporting
confidence: 52%
“…Work related to beliefs about mental disorders finds that laypeople treat mental disorders as if they do have causal essences, while clinicians do not-differences that may be attributable to expertise (Ahn, Flanagan, Marsh, & Sanislow, 2006). To test whether reduced beliefs in essences are indicative of an overall influence of expertise or a demonstration of a phenomenon specific to expertise in the mental health domain we compared beliefs about mental and medical disorders held by practicing physicians (n = 43; 19 primary care and 24 non-psychiatry specialists) and laypeople (n = 40).…”
mentioning
confidence: 98%
“…Although essentialism is often criticized as biologically inaccurate (Bohan 1993;Mayr 1991;Sober 1994;Wilson 1999), it nonetheless persists in everyday reasoning. Essentialist reasoning has been found in the USA among both children (Gelman 2003;Giles 2003;Heyman and Gelman 2000;Hirschfeld 1996;Taylor 1996) and adults (Ahn et al 2006;Atran 1998;Haslam 1998;Haslam and Ernst 2002;Haslam et al 2000;Rehder 2007), and in other cultural contexts as well (Astuti et al 2004;Diesendruck 2001;Diesendruck and Gelman 1999;Gil-White 2001;Mahalingam 1998). The purpose of the present studies is to examine some of the factors that encourage gender essentialism in the USA, by asking which gender concepts are essentialized and who essentializes gender.…”
Section: Introductionmentioning
confidence: 96%